Agenda for future business resilience and survival avenues in crisis times: A systematic literature review of the effects of COVID-19 on SMEs’ productivity in South Africa - Nokuphila Yvonne Biyela; Reward Utete (Social Sciences and Humanities Open)
For handling future crises and to give their businesses the best chance of survival it is imperative that owners and managers of SMEs have a comprehensive understanding of the severity of the impact of the crisis itself. Despite the criticality of SMEs to the economy, there is lack of concerted evidence regarding the impact of COVID-19 on small and medium enterprises' productivity in South Africa. Hence, the study sought to integrate the existing literature to attain a composite view of the impact of COVID-19 on small and medium enterprises’ productivity in South Africa. A systematic literature review of (35) articles published during the COVID-19 pandemic years of 2020–2022 revealed a common set of labour, capital, and total factor productivity issue concerns impacting SMEs across industry designations in South Africa. But out of these concerns have emerged a set of business resilience strategies and policy implications that offer SMEs the strategic ability to prepare ahead of time for crises situations and come out stronger.